Starch-based composite solid acid, its synthesis method and catalytic application
Patent Information
- Application Number
- CN202611477594.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]本发明的目的在于解决现有碳基固体酸磺酸基负载量低、活性位点易脱落、催化活性不足的问题,提供一种高酸量、高稳定性的淀粉基复合型固体酸的合成方法
[0017]综上,目前尚没有将ZrO2与稀土元素进行双掺杂协同改性淀粉基碳固体酸的报道,二者协同调控碳基体结构与酸性位点的作用机制尚未被揭示,及其在生物柴油制备领域的具体应用技术方案,相关技术空白尚未被填补。
Smart Images

Figure CN122974336A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of industrial catalysis technology, specifically relating to a starch-based composite solid acid, its synthesis method, and its catalytic applications. Background Technology
[0002] With the development of the biodiesel industry, utilizing low-cost, high-yield non-edible oils (such as waste cooking oil) to replace edible oils in biodiesel production is of great and far-reaching significance. Transesterification is one of the core technologies in biodiesel production, and catalyst performance is a key influencing factor. However, traditional homogeneous catalysts suffer from severe equipment corrosion, difficulties in product separation, and challenges in catalyst recovery, significantly hindering their industrialization. Solid acid catalysts have successfully overcome the separation defects of homogeneous catalysts, but their catalytic activity still needs improvement, especially in enhancing reaction selectivity, reducing environmental impact, and achieving process sustainability. Metal oxide-based solid acid catalysts can be applied to high-acid-value feedstocks, but the reactions often require harsh high temperatures or long reaction times.
[0003] In the prior art, patent publication number CN113522345A (titled "Ordered mesoporous Al-SBA-15 supported zirconia sulfate solid acid material and its preparation and application") discloses an ordered mesoporous Al-SBA-15 supported zirconia sulfate solid acid catalyst, which has the advantages of adjustable acid strength and excellent catalytic stability. However, because the reaction needs to be carried out at a high temperature of 140℃ (significantly higher than conventional mild reaction conditions), the energy consumption is high, and the preparation process is cumbersome, increasing the cost and limiting the economics of large-scale application. Patent publication number CN115999594A (titled "A Ce-based rare earth composite solid strong acid catalyst for biodiesel and its preparation process") discloses... The first case discloses a Ce-based rare earth composite solid strong acid catalyst, which has the advantages of automatic separation from liquid products and simple post-processing, but suffers from cumbersome process steps and high raw material costs. The second case, patent publication number CN119565593A (titled "A solid acid catalyst and its preparation method and application"), discloses a rare earth modified solid acid catalyst, which has the advantages of strong resistance to carbon deposition and loss of active centers, and is suitable for high-acid-value waste oils. However, its preparation requires a two-step impregnation-calcination process, which is complex and energy-intensive. The third case, patent publication number CN103706384A (titled "A method for preparing a biodiesel catalyst"), discloses rare earth La-doped nano-PO4. 2- ZrO2 catalyst, through rare earth doping, improves selectivity and is suitable for raw materials such as *Sapindus mukorossi* seed oil. However, due to long-term recycling, PO4 content decreases. 2- It is easily lost, leading to a significant decrease in catalytic efficiency.
[0004] In recent years, the research and application of carbon-based solid acids have increased significantly. Biomass, as an ideal carbon source, can form a partially graphitized layered molecular structure through carbonization. This layered graphite structure is conducive to the stable grafting of sulfonic acid groups. However, biomass-derived solid acid catalysts still have defects, with their total acid value being only 0.99-3.80 mmol / g. On the one hand, the complex graphitization process makes it difficult to control the internal structure, and most importantly, increasing the loading of -SO3H groups faces a great technical challenge; on the other hand, excessive disorder of structural units leads to poor reproducibility, and -SO3H groups are easy to detach, resulting in poor performance. In the prior art, the technical solution disclosed in patent publication number CN112552995A (titled "Method for producing biodiesel from microalgae oils catalyzed by microalgae carbon-based magnetic solid acid catalyst") discloses a microalgae carbon-based magnetic solid acid catalyst, which has the advantage of low energy consumption, but its application is limited by the reliance on microwave equipment for the reaction.
[0005] Using starch as a carbon source can solve the above problems to some extent. The repeating structural units of starch are composed of glucose monomers, which are rich in hydroxyl structures, giving them strong hydrophilicity. This characteristic is beneficial for in-situ doping of metal salts in aqueous solution in the form of oxides or metal ions. Studies have shown that the presence of metal ions or metal oxides can affect the formation and functionality of carbon-based structures. In the prior art, the technical solution of patent publication number CN102698796A (titled "A method for preparing a honeycomb carbon-based solid acid catalyst") uses carbon-based materials such as starch and sucrose as raw materials to prepare solid acid catalysts. It has the advantages of simple process, low preparation cost, reusability, and convenient operation. However, due to the single component, it is prone to over-carbonization or insufficient carbonization due to temperature fluctuations, resulting in unstable catalytic performance. Summary of the Invention
[0006] The purpose of this invention is to solve the problems of low sulfonic acid loading, easy loss of active sites, and insufficient catalytic activity in existing carbon-based solid acids, and to provide a method for synthesizing starch-based composite solid acids with high acid content and high stability.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for synthesizing a starch-based complex solid acid includes the following steps: (1) Mix starch and metal salt solution evenly, stir at 500 rpm for 30 min, let stand to form, and dry at 80-100℃ for 2 h to obtain biomass precursor material; The solute in the metal salt solution includes ZrOCl2·8H2O and rare earth metal salts, wherein the rare earth metal salts are selected from one of La(NO3)3·6H2O, Ce(NO3)3·6H2O, Gd(NO3)3·6H2O, and Dy(NO3)3·6H2O. The mass ratio of starch to water, the solvent used to prepare the metal salt solution, is 2:1. (2) Carbonize the biomass precursor material in a nitrogen atmosphere at 500-600℃ for 4 hours, then crush it and sieve it through a 200-mesh screen to obtain a composite mesoporous carbon material. (3) The composite mesoporous carbon material was added to 98% concentrated sulfuric acid at a mass-volume ratio of 1g:4-5mL and sulfonated at 140℃ for 12-18h. After the reaction was completed, the solid-liquid mixture was diluted with 3-4 times the volume of anhydrous ethanol, settled for 1h, the supernatant was removed, filtered and washed, and dried at 80℃ for 1h to obtain starch-based composite solid acid.
[0008] This invention involves co-doping ZrOCl2·8H2O with rare earth metal salts into a starch-based carrier, followed by carbonization to form a composite mesoporous carbon material. Due to the hydroxyl groups in starch, the metal element Zr and the rare earth element R are uniformly dispersed in the carbon matrix, resulting in a similar content of disordered and ordered carbon. D / I G The ratio is close to 1. In addition, the carbon material has a high loading of sulfonic acid groups (-SO3H), which enhances the stability of the active sites through synergistic effects with metal compounds. The abundant oxygen-containing groups in the carbon material improve the catalyst's affinity for oily substrates, thereby solving the problems of low catalytic efficiency and poor stability of existing carbon-based solid acid catalysts.
[0009] The specific synergistic mechanism is as follows: ZrOCl2·8H2O is converted into amorphous ZrO2 during carbonization, which can form stable chemical bonds with the carbon matrix formed by starch carbonization. Simultaneously, rare earth elements (R...)... 3+ The complex structure formed by the carbon and ZrO2 synergistically regulates the graphitization degree of the carbon matrix, which can improve the Raman spectrum of the composite mesoporous carbon material. D / I G The ratio remained between 0.99 and 1.08. This range of structural disorder ensured the structural stability of the carbon matrix and provided ample sites for the grafting of sulfonic acid groups (-SO3H) during subsequent sulfonation, resulting in a total acid content of 4.55-5.25 mmol / g, significantly higher than existing single-carbon-based solid acids (0.99-3.80 mmol / g). Furthermore, rare earth elements (R...) 3+ The ZrO2 forms a stable coordination bond with the sulfonic acid group (-SO3H), which inhibits the removal of the sulfonic acid group during the reaction. At the same time, the Lewis acid site of ZrO2 and the Brønsted acid site of the sulfonic acid group work together to enhance the stability of the active site of the catalyst. The oxygen-containing groups in the carbon material improve the affinity of the catalyst for triglycerides in oils, thereby improving the catalytic activity and cycle stability (at a temperature of 104℃, a biodiesel yield of 98.33% can be achieved after 4 hours of reaction, and the biodiesel yield is still maintained at over 95% in the sixth cycle).
[0010] In a preferred example, in step (1), the theoretical mass ratio of C:ZrO2:rare earth element R in the composite mesoporous carbon material (based on complete starch carbonization) is 20:0.5-3:0.05-0.15, and the rare earth element R is one of La, Ce, Gd, and Dy.
[0011] In a preferred example, in step (3), the sulfonation time is 12-18h.
[0012] In a preferred example, in step (3), the volume ratio of the solid-liquid mixture to anhydrous ethanol is 1:3-4, the settling time is 1h, and the mixture is dried at 80°C for 1h.
[0013] Based on a general inventive concept, another object of the present invention is to provide a starch-based composite solid acid obtained by the above-described synthetic method and its catalytic application in the transesterification process for the preparation of biodiesel; The starch-based composite solid acid has a total acidity of 4.55-5.25 mmol / g, ZrO2 and rare earth element R are uniformly dispersed in the carbon matrix, and the sulfonic acid group (-SO3H) loading is ≥2.0 mmol / g; preferably, Raman spectroscopy I... D / I G The ratio is 0.99-1.08. The raw materials for biodiesel production via transesterification include at least one of waste cooking oil, vegetable oil, and animal fat.
[0014] Preferably, the biodiesel prepared by transesterification is a fatty acid methyl ester, using waste cooking oil that conforms to the industry standard NB / T 13007-2021 "Biodiesel (BD100) Raw Material Waste Oil" as raw material.
[0015] This invention first mixes metal salt and rare earth salt solution with starch-based powder to obtain a biomass-doped precursor. Then, the biomass precursor material is carbonized to prepare a composite mesoporous carbon material, and then sulfonated to obtain a starch-based composite solid acid.
[0016] Two related technical solutions are disclosed in the prior art: one is carbon-based solid acid catalysts modified with rare earth elements (such as lanthanum, cerium, etc.), which improve the bonding stability between the carbon-based support and the acidic sites by forming stable coordination bonds with acidic groups through rare earth elements, and is used to prepare biodiesel from high-acid-value oils; the other is carbon-based solid acid catalysts modified with zirconium dioxide and / or titanium dioxide to enhance the mechanical stability of the catalyst. However, neither involves the technical concept of co-doping and synergistic modification of carbon-based supports with rare earth elements and zirconium dioxide: there are no patents or literature reports that clearly use "rare earth-zirconium dioxide co-doping" as the core strategy to prepare carbon-based solid acid catalysts, nor are there any precedents for the application of such co-doped modified carbon-based solid acid catalysts in biodiesel synthesis (including esterification and acid reduction of high-acid-value oils, triglyceride transesterification, and mixed feed conversion reaction processes).
[0017] In summary, there are currently no reports on the synergistic modification of starch-based carbon solid acids by dual doping of ZrO2 and rare earth elements. The mechanism by which the two synergistically regulate the carbon matrix structure and acidic sites has not yet been revealed, nor has the specific application technology in the field of biodiesel preparation been established. The relevant technological gaps have not yet been filled.
[0018] The method of this invention is relatively simple and operates under mild conditions. The synthesized starch-based composite solid acid (catalyst) exhibits excellent catalytic performance. In the catalytic preparation of biodiesel, the reaction conditions are mild, the separation method is simple to operate, the catalytic effect is good, and the cost is low, which can greatly improve the conversion rate of raw materials and increase the yield of biodiesel. In the catalytic transesterification reaction of waste cooking oil, the starch-based composite solid acid of this invention achieved a high biodiesel yield (98.33%) at a relatively low temperature (104℃) and in a short time (4h), indicating that the catalyst has high activity, superior to most solid acid catalysts.
[0019] Furthermore, when the catalyst of this invention is recycled, after being washed three times with anhydrous ethanol and dried at 80°C for 1 hour, it can be reused. After six cycles, the biodiesel yield still remains above 95%, demonstrating high stability. In summary, the catalytic activity and stability of this solid acid are significantly superior to the technologies disclosed in most existing patents and literature. Attached Figure Description
[0020] Figure 1 The image shows the 1H NMR spectrum of the biodiesel product prepared in Example 1. The peak at δ=3.66ppm corresponds to the characteristic peak of -OCH3 (methyl hydrogen) in fatty acid methyl ester. The peaks at δ=0.88ppm, 1.26ppm, and 1.60ppm correspond to the peaks of methyl and methylene hydrogen on the fatty acid chain, respectively. The peak at δ=2.30ppm corresponds to the characteristic peak of α-hydrogen (methylene hydrogen) on the ester group of the fatty acid chain, proving that the product is the target product, fatty acid methyl ester. Figure 2The XRD characterization diagram of the starch-based composite solid acid catalyst in Example 7 shows no characteristic crystal diffraction peaks, indicating that the metal oxide is uniformly dispersed in the carbon material in an amorphous state. Figure 3 The image shows the EDS-Mapping of the starch-based composite solid acid catalyst (internal sample number: MZD101) in Example 7. (a) is a color SEM image of the MZD101 particles; (b) is the corresponding grayscale SEM image; (c) shows the EDS energy spectrum and elemental mass percentage composition of MZD101, indicating the presence of C, O, S, Zr, and Dy; (d)–(h) are elemental surface scan distribution maps of C, O, S, Zr, and Dy, demonstrating the uniform dispersion of each element on the catalyst particles. The uniform dispersion of zirconium and dysprosium on the carbon material surface fully confirms... Figure 2 The XRD analysis results show that sulfur is uniformly distributed within the carbon framework, indicating the uniform grafting of sulfonic acid groups in the catalyst. Figure 4 The image shows the Raman spectrum characterization of the starch-based composite solid acid catalyst in Example 7; I was measured. D / I G The ratio can be used to evaluate the presence of a moderate degree of structural disorder in the catalyst; Figure 5 This serves as a verification of the recycling of the starch-based composite solid acid catalyst in Example 7; after 6 cycles, the biodiesel yield is still higher than 95%. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention is further described in conjunction with specific embodiments. However, this invention is not limited to these embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments. In this invention, unless otherwise specified, the equipment and raw materials used are commercially available or commonly used in the art. Unless otherwise specified, the methods in the following embodiments are conventional methods in the art.
[0022] The terms “comprising,” “including,” “containing,” or any other variations thereof, as used herein, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.
[0023] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether such range is disclosed individually. For example, when the range “1 to 5” is disclosed, the described range should be interpreted as including ranges “1 to 4”, “1 to 3”, “1 to 2”, “1 to 2 and 4 to 5”, “1 to 3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within the range.
[0024] Example 1 1. Preparation of starch-based composite solid acid (1) According to the theoretical mass ratio of C∶ZrO2∶La=20∶1∶0.1, add 150g of starch to a large beaker for later use, add 7.85g of ZrOCl2·8H2O and 0.94g of La(NO3)3·6H2O, and then add 75mL of water to completely dissolve the salt and prepare a solution for later use; while stirring, add the solution to the starch, stir at 500rpm for 30min, let it stand to form, and then dry it at 80℃ for 2h for later use; (2) The biomass precursor material was placed in a crucible and carbonized at 500°C for 4 hours under a nitrogen atmosphere, and then crushed to obtain a composite mesoporous carbon material. (3) 20g of composite mesoporous carbon material was added to 100mL of concentrated sulfuric acid (98%) and sulfonated at 140℃ for 16h. After the reaction was completed, 400mL of anhydrous ethanol was added for dilution, and the mixture was allowed to settle for 1h. The supernatant was removed, and the mixture was filtered and washed repeatedly until the washing liquid was neutral. The mixture was dried at 80℃ for 1h to obtain starch-based composite solid acid (catalyst 1).
[0025] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 1) was added, and the mixture was stirred at 104 °C for 4 h. After the reaction was completed, 4 mL of ethyl acetate was added to reduce the viscosity of the system. The solid catalyst was separated by centrifugation, and the filtrate was separated. The supernatant was collected, and ethyl acetate and unreacted methanol were removed by rotary evaporation. Glycerol was removed by washing with 4 mL of hot water, and then the upper product was dissolved with 6 mL of ethyl acetate to remove the aqueous phase. Finally, the ethyl acetate solution of biodiesel was dried with anhydrous sodium sulfate, and then ethyl acetate was removed by rotary evaporation to obtain purified biodiesel. Yield was calculated using the 1H NMR-relative internal standard method (with deuterated chloroform as solvent and tetramethylsilane (TMS) as internal standard), by the integral area ratio of the characteristic peak of fatty acid methyl ester -OCH3 at δ=3.66ppm to that of triglyceride ester α-hydrogen (methylene) -OCOCH2- at δ=2.30ppm. The yield was 96.90%.
[0026] Example 2 1. Preparation of starch-based composite solid acid As in Example 1, catalyst 1 was obtained; 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 1) was added. The reaction was carried out at 110 °C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 97.75% by 1H NMR spectroscopy-relative internal standard method.
[0027] Example 3 1. Preparation of starch-based composite solid acid (1) According to the theoretical mass ratio of C∶ZrO2∶Ce=20∶1∶0.1, add 150g of starch to a large beaker for later use, add 7.85g of ZrOCl2·8H2O and 0.93g of Ce(NO3)3·6H2O, and then add 75mL of water to completely dissolve the salt and prepare a solution for later use; other steps are the same as in Example 1; (2) Same as Example 1; (3) Same as Example 1, except that the amount of concentrated sulfuric acid used is 80 mL, the sulfonation time is 18 h, and it is diluted with 320 mL of anhydrous ethanol to obtain catalyst 2.
[0028] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 2) was added. The reaction was carried out at 104 °C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 96.48% by 1H NMR spectroscopy-relative internal standard method.
[0029] Example 4 1. Preparation of starch-based composite solid acid As in Example 3, catalyst 2 was obtained; 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 2) was added. The reaction was carried out at 100°C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 85.47% by 1H NMR spectroscopy-relative internal standard method.
[0030] Example 5 1. Preparation of starch-based composite solid acid (1) According to the theoretical mass ratio of C∶ZrO2∶Gd=20∶1∶0.1, add 150g of starch to a large beaker for later use, add 7.85g of ZrOCl2·8H2O and 0.86g of Gd(NO3)3·6H2O, and then add 75mL of water to completely dissolve the salt and prepare a solution for later use; while stirring, add the solution to the starch, stir at 500rpm for 30 min, let it stand to form, and then dry it at 100℃ for 2h for later use; (2) Same as Example 1; (3) 20g of composite mesoporous carbon material was added to 80mL of concentrated sulfuric acid (98%) and sulfonated at 140℃ for 12h. After the reaction was completed, 320mL of anhydrous ethanol was added for dilution, and the mixture was allowed to settle for 1h. The supernatant was removed, and the mixture was filtered and washed repeatedly until the washing liquid was neutral. The mixture was dried at 80℃ for 1h to obtain catalyst 3.
[0031] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 3) was added. The reaction was carried out at 104 °C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 96.76% by 1H NMR spectroscopy-relative internal standard method.
[0032] Example 6 1. Preparation of starch-based composite solid acid As in Example 5, catalyst 3 was obtained; 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 3) was added. The reaction was carried out at 94 °C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 61.73% by 1H NMR spectroscopy-relative internal standard method.
[0033] Example 7 1. Preparation of starch-based composite solid acid (1) According to the theoretical mass ratio of C∶ZrO2∶Dy=20∶1∶0.1, add 150g of starch to a large beaker for later use, add 7.85g of ZrOCl2·8H2O and 0.84g of Dy(NO3)3·6H2O, and then add 75mL of water to completely dissolve the salt and prepare a solution for later use; while stirring, add the solution to the starch, stir at 500rpm for 30min, let it stand to form, and then dry it at 90℃ for 2h for later use; (2) Same as Example 1; (3) Same as in Example 1, catalyst 4 was obtained.
[0034] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 4) was added. The reaction was carried out at 104 °C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 98.33% by 1H NMR spectroscopy-relative internal standard method.
[0035] Example 8 1. Preparation of starch-based composite solid acid As in Example 7, catalyst 4 was obtained; 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 24:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 4) was added. The reaction was carried out at 100°C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 94.16% by 1H NMR spectroscopy-relative internal standard method.
[0036] Example 9 1. Preparation of starch-based composite solid acid As in Example 7, catalyst 4 was obtained; 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 21:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 4) was added. The reaction was carried out at 94 °C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 70.77% by 1H NMR spectroscopy-relative internal standard method.
[0037] Example 10 1. Preparation of starch-based composite solid acid (1) Same as Example 7, except that the zirconium content is changed (theoretical mass ratio is C∶ZrO2∶Dy=20∶0.5∶0.1); (2) Same as Example 7; (3) Same as in Example 7, catalyst 5 was obtained.
[0038] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 5) was added. The reaction was carried out at 94°C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 55.56% by 1H NMR spectroscopy-relative internal standard method.
[0039] Example 11 1. Preparation of starch-based composite solid acid (1) Same as Example 7, except that the zirconium content is changed (theoretical mass ratio is C∶ZrO2∶Dy=20∶3∶0.1); (2) Same as Example 7; (3) Same as in Example 7, catalyst 6 was obtained.
[0040] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 6) was added. The reaction was carried out at 94°C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 50.85% by 1H NMR spectroscopy-relative internal standard method.
[0041] Examples 10 and 11 illustrate that both excessively high and low ZrO2 mass ratios can lead to a decrease in catalytic performance, possibly because the content deviates from the optimal range, reducing the number of active sites and thus decreasing catalytic activity.
[0042] Example 12 1. Preparation of starch-based composite solid acid (1) Same as Example 7, except that the dysprosium content is changed (theoretical mass ratio is C∶ZrO2∶Dy=20∶1∶0.05); (2) Same as Example 7; (3) Same as in Example 7, catalyst 7 was obtained.
[0043] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 7) was added. The reaction was carried out at 100°C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 92.46% by 1H NMR spectroscopy-relative internal standard method.
[0044] Example 13 1. Preparation of starch-based composite solid acid (1) Same as Example 7, except that the dysprosium content is changed (theoretical mass ratio is C∶ZrO2∶Dy=20∶1∶0.15); (2) Same as Example 7; (3) Same as in Example 7, catalyst 8 was obtained.
[0045] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 8) was added. The reaction was carried out at 100°C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 91.83% by 1H NMR spectroscopy-relative internal standard method.
[0046] Example 14 1. Preparation of starch-based composite solid acid (1) Same as Example 1, except that only zirconium is added for modification (theoretical mass ratio is C∶ZrO2∶Dy=20∶1∶0); (2) Same as Example 1; (3) Same as in Example 1, catalyst 9 was obtained.
[0047] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 9) was added. The reaction was carried out at 94°C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 44.15% by 1H NMR spectroscopy-relative internal standard method.
[0048] The catalytic activity of the single-doped ZrO2 sample was significantly lower, which may be due to its I content. D / I G =0.79 is too low, the degree of graphitization is too high, and there are too few sites for grafting sulfonic acid groups, resulting in insufficient catalytic performance.
[0049] Example 15 1. Preparation of starch-based composite solid acid As in Example 14, catalyst 9 was obtained.
[0050] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 9) was added. The reaction was carried out at 100°C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 67.41% by 1H NMR spectroscopy-relative internal standard method.
[0051] Example 16 1. Preparation of starch-based composite solid acid (1) Same as Example 7, except that zirconium salt is not added (theoretical mass ratio is C∶ZrO2∶Dy=20∶0∶0.1); (2) Same as Example 7; (3) Same as in Example 7, catalyst 10 was obtained.
[0052] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 10) was added. The reaction was carried out at 94 °C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 54.29% by 1H NMR spectroscopy-relative internal standard method.
[0053] Single-doped Dy sample, I D / I G =1.10 is too high, so the increase in the number of active sites for graftable sulfonic acid groups is limited.
[0054] Example 17 1. Preparation of starch-based composite solid acid (1) Same as Example 1, except that zirconium and dysprosium salts are not added (theoretical mass ratio is C∶ZrO2∶Dy=20∶0∶0); (2) Same as Example 1; (3) Same as in Example 1, catalyst 11 was obtained.
[0055] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 11) was added. The reaction was carried out at 94 °C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 51.84% by 1H NMR spectroscopy-relative internal standard method.
[0056] Carbon catalyst samples without zirconium and rare earth elements, I D / I G =0.94 is relatively low, retaining intrinsic characteristics, with fewer active sites for graftable sulfonic acid groups, resulting in lower catalytic activity. Combining Examples 14 and 7, it can be seen that adding zirconium can promote the graphitization degree of the carbon material, thereby reducing catalytic activity; when both zirconium and rare earth elements are added, they interact, avoiding the formation of the aforementioned adverse factors, thus improving the I... D / I G The ratio is close to 1, indicating good catalytic activity.
[0057] Example 18 1. Preparation of starch-based composite solid acid As in Example 17, catalyst 11 was obtained.
[0058] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 11) was added. The reaction was carried out at 100°C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 69.01% by 1H NMR spectroscopy-relative internal standard method. Compared with Example 17, the biodiesel yield increased by about 17% with increasing reaction temperature, but it was still below 70%. Compared with Example 8, the yield of catalyst 4, which is doped with zirconium and rare earth bimetals, was significantly lower at 94.16%, indicating that the metals played a modifying role.
[0059] Example 19 1. Preparation of starch-based composite solid acid As in Example 7, catalyst 4 was obtained; 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of blended edible vegetable oil (Jinlongyu brand, Yihai Kerry (Nanchang) Grain and Oil Food Co., Ltd.) were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 4) was added. The reaction was carried out at 100°C with stirring for 4 hours. After the reaction was completed, the treatment method was the same as in Example 1. The yield was calculated to be 95.26% by 1H NMR spectroscopy-relative internal standard method.
[0060] Example 20 1. Preparation of starch-based composite solid acid (1) Same as Example 7; (2) The biomass precursor material was placed in a crucible and carbonized at 600°C for 4 hours in a nitrogen atmosphere, and then crushed to obtain a composite mesoporous carbon material. (3) Same as in Example 7, catalyst 12 was obtained.
[0061] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 12) was added. The reaction was carried out at 104 °C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 97.37% by 1H NMR spectroscopy-relative internal standard method. Compared with Example 7, this shows that the performance did not change significantly after the carbonization temperature was increased from 500 °C to 600 °C.
[0062] Example 21 1. Preparation of starch-based composite solid acid (1) Same as Example 3, except that it is dried at 100°C for 2 hours; (2) Same as Example 3, except that it is at 550°C; (3) 20g of composite mesoporous carbon material was added to 100mL of concentrated sulfuric acid (98%) and sulfonated at 140℃ for 16h. After the reaction was completed, 300mL of anhydrous ethanol was added for dilution, and the mixture was allowed to settle for 1h. The supernatant was removed, and the mixture was filtered and washed repeatedly until the washing liquid was neutral. The mixture was dried at 80℃ for 1h to obtain a composite solid acid catalyst (catalyst 13).
[0063] 2. Catalytic activity test First, 5.00 g of methanol and 5.00 g of waste cooking oil were added to a Schlenk tube, with a molar ratio of alcohol to oil of 27:1. Then, 0.25 g (5% by mass of oil) of a composite solid acid catalyst (catalyst 13) was added. The reaction was carried out at 104 °C with stirring for 4 hours. After the reaction, the treatment method was the same as in Example 1. The yield was calculated to be 97.01% by 1H NMR spectroscopy-relative internal standard method. Compared with Example 3, the composite catalyst has higher activity.
[0064] Test Example 1 The total acid content was determined by acid-base titration: 0.1 g of catalyst was accurately weighed, 20 mL of 0.1 mol / L NaOH solution was added, the mixture was stirred at room temperature for 2 h, the supernatant was collected by centrifugation, and titrated with 0.1 mol / L HCl standard solution until phenolphthalein decolorized. The total acid content was then calculated.
[0065] Examples 10-13 are parallel experiments of the optimal doping ratio, corresponding to catalysts 5-8; Examples 14-18 (catalysts 9-11) are parallel experiments of single doping and blank control in Examples 7-9 (catalyst 4), and the results are shown in Table 1 below; Table 1:
[0066] The total acidity of the starch-based composite solid acids prepared in Examples 3 and 7 was 4.55-5.25 mmol / g, which was superior to the carbon-based solid acids with single metal or no metal modification in Examples 14-18 (catalysts 9-11) (3.50-3.75 mmol / g), and also significantly higher than existing carbon-based solid acids (0.99-3.80 mmol / g). After repeated transesterification reactions and recycling, the degree of local disorder in the carbon matrix of the catalyst changed slightly.
[0067] The comparison results of the present invention with other existing disclosed technologies in terms of catalytic performance (measured by biodiesel yield) and cycle stability (evaluated by catalyst cycle number and cycle yield) are shown in Table 2 below; Table 2:
[0068] By setting up 21 examples covering different rare earth elements, doping ratios, and reaction conditions, and through comparisons of single doping (catalysts 9-10), a blank control (catalyst 11), and dual doping (catalysts 1-8), the synergistic advantages of dual doping are highlighted. The performance degradation of single-doped ZrO2 is attributed to the excessive graphitization of the carbon matrix caused by single-doped Zr. D / I G(0.79) reduced the number of marginal grafting sites, resulting in insufficient -SO3H grafting. Meanwhile, comparison with existing technical literature data verified the superior catalytic activity and stability.
[0069] The synthesis process of this invention is simple, the reaction mechanism is clear, the reaction device is simple, the conditions are relatively mild, the separation method is easy to operate, the catalytic effect is good, and the cost is low.
[0070] The above embodiments are merely preferred embodiments of the present invention. Any simple modifications, alterations, and substitutions made to the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.
Claims
1. A method for synthesizing a starch-based complex solid acid, characterized in that, Includes the following steps: (1) Mix starch and metal salt solution evenly, stir at 500 rpm for 30 min, let stand to form, and dry at 80-100℃ for 2 h to obtain biomass precursor material; wherein, the solute of metal salt solution includes ZrOCl2·8H2O and rare earth metal salt, wherein the rare earth metal salt is selected from one of La(NO3)3·6H2O, Ce(NO3)3·6H2O, Gd(NO3)3·6H2O, and Dy(NO3)3·6H2O; the mass ratio of starch to water used to prepare metal salt solution is 2:1; (2) Carbonize the biomass precursor material in a nitrogen atmosphere at 500-600℃ for 4 hours, then crush it and sieve it through a 200-mesh screen to obtain a composite mesoporous carbon material. The theoretical mass ratio of C:ZrO2:rare earth element R in the composite mesoporous carbon material (based on complete starch carbonization) is 20:0.5-3:0.05-0.15, and the rare earth element R is one of La, Ce, Gd, and Dy. (3) The composite mesoporous carbon material was added to 98% concentrated sulfuric acid at a mass-volume ratio of 1g:4-5mL and sulfonated at 140℃. After the reaction was completed, anhydrous ethanol was added to dilute the solid-liquid mixture, and the mixture was allowed to settle. The supernatant was removed, filtered, washed, and dried to obtain starch-based composite solid acid.
2. The method for synthesizing a starch-based composite solid acid according to claim 1, characterized in that, In step (3), the sulfonation time is 12-18 hours.
3. The method for synthesizing a starch-based composite solid acid according to claim 1, characterized in that, In step (3), the volume ratio of the solid-liquid mixture to anhydrous ethanol is 1:3-4, the sedimentation time is 1h, and the mixture is dried at 80℃ for 1h.
4. A starch-based complex solid acid obtained by the synthesis method according to any one of claims 1-3, characterized in that: The total acidity of the starch-based composite solid acid is 4.55-5.25 mmol / g, ZrO2 and rare earth element R are uniformly dispersed in the carbon matrix, and the sulfonic acid loading is ≥2.0 mmol / g.
5. The catalytic application of the starch-based composite solid acid of claim 4 in the transesterification process for biodiesel production, characterized in that: The raw materials for biodiesel production via transesterification include at least one of waste cooking oil, vegetable oil, and animal fat.
6. The catalytic application according to claim 5, characterized in that: Biodiesel prepared by transesterification using waste cooking oil is a fatty acid methyl ester.
Citation Information
Patent Citations
Preparation method for honeycomb ceramic carbon-based solid acid catalyst
CN102698796A
Preparation method of bio-diesel catalyst
CN103706384A
Method for preparing biodiesel by catalyzing microalgal oil with microalgal carbon-based magnetic solid acid catalyst
CN112552995A
Ordered mesoporous Al-SBA-15 loaded sulfated zirconium oxide solid acid material, and preparation and application thereof
CN113522345A
Ce-series rare earth composite solid strong acid catalyst for biodiesel and preparation process of Ce-series rare earth composite solid strong acid catalyst
CN115999594A